Nutrient depletion in the agricultural soils of Africa - Henao, Julio; Baanante, Carlos A. (International Food Policy Research Institute, 1999)
About two-thirds of Africans depend on agriculture for their livelihoods. The fate of agricultural production, therefore, directly affects economic growth, social improvement, and trade in Africa. As the region's population continues to grow rapidly, outpacing the growth rate in other regions of the world, its agriculturalland is becoming increasingly degraded. Farmers are intensifying land use to meet food needs without proper management practices and external inputs.